2021
DOI: 10.1016/j.xcrm.2021.100219
|View full text |Cite
|
Sign up to set email alerts
|

A single-cell atlas of the healthy breast tissues reveals clinically relevant clusters of breast epithelial cells

Abstract: Highlights d Healthy breast contains 23 subclusters of epithelial cells d Breast cancers may originate from 3 luminal mature and 1 progenitor subclusters d TBX3 and PDK4, co-expressed with estrogen receptor (ER), subclassify ER+ breast cancers

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(83 citation statements)
references
References 69 publications
3
80
0
Order By: Relevance
“…Only, Azizi et al performed sorting on CD45 pos immune cells from breast cancer patients undergoing mastectomy before encapsulation ( 18 ). As a consequence, most studies describe the epithelial cell composition in tumorigenic micro-environment ( 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Only, Azizi et al performed sorting on CD45 pos immune cells from breast cancer patients undergoing mastectomy before encapsulation ( 18 ). As a consequence, most studies describe the epithelial cell composition in tumorigenic micro-environment ( 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Seeking to understand why TAD signatures provided additional discriminative power, we drilled deeper into the breast tissue data. A particular challenge there is distinguishing between progenitor and mature luminal cells: there are some sub-populations of cells that are transcriptionally similar overall, but where Bhat-Nakshatri et al's expert knowledge of relevant marker genes allowed them to distinguish between progenitor and mature luminal cells [51]. We found that TAD signatures were particularly helpful in these ambiguous situations, enabling more accurate distinction between mature luminal cells and progenitor cells (Methods, Figure 5C).…”
Section: Less-differentiated and Cancer Cells Exhibit Greater Clustering Of Expression Into Tadsmentioning
confidence: 76%
“…Applying the Leiden algorithm for cell clustering, we compared the biological accuracy of the clustering results computed from three input representations of scRNA-seq observations: raw RNA-seq data (generated by applying principal component analysis, PCA, on transcript count data); TAD signatures (by applying PCA on log-odds of TAD activation probabilities); and a concatenation of the two. On three large scRNA-seq datasets sourced from the Chan-Zuckerberg Biohub's cellXgene portal [50], covering breast [51], lung [52] and T cells [53], we compared the overlap between the automatically-computed cell clusters and the expertly-annotated cell type labels made available by the original study authors (Figure 5B, Methods). We found that using TAD signatures led to cell clusters that better agreed with expert labels and in all cases, the representation that combined raw RNA-seq and TAD signatures performed at least as well as the RNA-seq-only representation.…”
Section: Less-differentiated and Cancer Cells Exhibit Greater Clustering Of Expression Into Tadsmentioning
confidence: 99%
See 1 more Smart Citation
“…This atlas is based on single-cell RNA-seq and is useful to derive breast epithelial cell subcluster-specific gene expression signatures, which can be applied to breast cancer gene expression data to identify putative cell-of-origin. For complete details on the use and execution of this protocol, please refer to Bhat-Nakshatri et al. (2021) .…”
mentioning
confidence: 99%